ANALISIS KEPEMIMPINAN KEPALA SEKOLAH, FASILITAS DAN LINGKUNGAN BELAJAR TERHADAP KINERJA GURU SMK DI KABUPATEN BIREUEN - Win, Dahliani; Raihan (IndOmera, 2022)
This study aims to determine the influence of principals' leadership on learning facilities and a shared learning environment – ​​Likewise with teacher performance in vocational schools throughout Bireuen Regency. The research was conducted by means of a survey of 184 teachers who are employees of Vocational High Schools (SMK) throughout Bireuen Regency, with data collection through questionnaires. And data analysis technique through path analysis approach. The results of the study found 1) There was a positive influence of the principal's leadership aspect on the performance of SMKN teachers throughout Bireuen Regency, which was 11.57%. 2) It is proven that there is a significant effect of learning facilities on teacher performance, either directly or indirectly, by 23.91%. 3) And also the results of statistical tests prove that there is a significant influence of learning environment factors on teacher performance at SMKN in Bireuen Regency which is calculated from this study, which is 8.16%. 4) The results of statistical measurements of the correlation coefficient and determination between the variables of Principal Leadership, Learning Facilities and Learning Environment on Teacher Performance stated that there was a significant effect. The contribution of these three factors is 43.60%. While the rest due to the role of variables that were not examined by 56.40%. These factors include performance allowances, non-financial compensation, communication, education and training, and others